Bayesian assessment of Lorenz and stochastic dominance. (25th April 2020) - Lander, David; Gunawan, David; Griffiths, William; Chotikapanich, Duangkamon
Abstract: We introduce a Bayesian approach for assessing Lorenz and stochastic dominance. For two income distributions, say X and Y, estimated via Markov chain Monte Carlo, we describe how to compute posterior probabilities for: (i) X dominates Y, (ii) Y dominates X and (iii) neither Y nor X dominates. The proposed approach is applied to Indonesian income distributions using mixtures of gamma densities that ensure flexible modelling. Probability curves depicting the probability of dominance at each population proportion are used to explain changes in dominance probabilities over restricted ranges relevant for poverty orderings. They also explain some seemingly contradictory outcomes from the p ‐values of some sampling theory tests. Résumé: Évaluation bayésienne des dominances stochastiques et de Lorenz . Dans cet article, nous présentons une approche bayésienne pour évaluer les dominances stochastiques et de Lorenz. Pour deux distributions de revenus estimées par la méthode de Monte‐Carlo par chaînes de Markov, X et Y par exemple, nous décrivons la fac¸on de calculer les probabilités à posteriori lorsque (i) X domine Y, (ii) Y domine X et (iii) ni Y ni X ne sont dominants. Nous avons appliqué l'approche proposée à la distribution des revenus en Indonésie en utilisant une variété de densités gamma pour garantir une modélisation flexible. Des courbes de probabilité illustrant la probabilité de dominance sur chaque proportion de population sont utilisées pour expliquer les changements de probabilité de dominance sur des fourchettes restreintes nécessaires à l'évaluation des niveaux de pauvreté. Ces courbes permettent également d'expliquer les résultats apparemment contradictoires des valeurs p de certains tests théoriques en matière d'échantillonnage.